Pengaruh Slogan, Konten Iklan, Dan Repetisi Iklan Terhadap Minat Beli Pada Marketplace Shopee (Studi Kasus Pada Pengguna Marketplace Shopee Di Kecamatan Purwosari Kabupaten Pasuruan) - Ubaidillah Ubaidillah; Eko Agus Alfianto (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2023)
The purpose of this research is to find out how much influence the slogan (X1), advertising content (X2), and advertisement repetition (X3) have on buying interest (Y). This study uses an explanatory research approach with quantitative methods. The data collection for this research was by distributing questionnaires to 110 respondents calculated using the machine and camble formula. The data analysis technique uses SPSS software version 16, in which the data will be processed, described and discussed to answer and prove the hypothesis proposed. The research results are as follows: (1). Slogan (X1) has no influence and is not significant to Purchase Intention (Y). (2). Advertising content (X2) has significant and significant effect on purchase intention (Y). (3). Advertisement repetition (X3) has significant and significant effect on buying interest (Y). (4) Slogans (X1), Advertising Content (X2), and Advertising Repeats (X3) have significant and significant effect on Purchase Intention (Y).